XVII. Study on the Impact of China’s Business Environment on Service Trade - Liu, Jiali; Wang, Weilong (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
With the upgrading of national economies, outward foreign direct investment (OFDI) and service trade have become increasingly vital to global trade. China’s economic restructuring has promoted high-quality growth in the service sector, making it a key driver of economic development. Studies show that a favourable business environment-transparent legal systems, efficient procedures, low business costs, and firm public services-can attract investment and talent, enhancing service trade performance. Such an environment reduces operational costs, improves efficiency, and fosters fair competition, enabling service trade enterprises to gain market share and improve profitability. This paper analyses the mechanisms through which the business environment affects service trade and proposes policy recommendations further to optimise conditions for sustainable growth in the sector.